Human toxoplasmosis: which biological diagnostic tests are best suited to which clinical situations?. Issue 9 (September 2013) - Murat, Jean-Benjamin; Fricker Hidalgo, Hélène; Brenier-Pinchart, Marie-Pierre; Pelloux, Hervé
The Toxoplasma gondii parasite is a worldwide threat most particularly in fetal life and immunosuppression. In most clinical situations (except in some ocular cases), correct detection or identification of toxoplasmosis requires biological analysis. This article considers the laboratory tools that have been developed in this field since the discovery of the pathogen, with emphasis on the most recent tests and how they can or should be used in different clinical situations. The authors also discuss the requirements and pitfalls that one should be aware of when biologically investigating this intriguing parasitosis.